2002
DOI: 10.1110/ps.32602
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the collagen triple helix model [(Pro‐Pro‐Gly)10]3

Abstract: The first report of the full-length structure of the collagen-like polypeptide [(Pro-Pro-Gly) 10 ] 3 is given. This structure was obtained from crystals grown in a microgravity environment, which diffracted up to 1.3 Å, using synchrotron radiation. The final model, which was refined to an R factor of 0.18, is the highestresolution description of a collagen triple helix reported to date. This structure provides clues regarding a series of aspects related to collagen triple helix structure and assembly. The stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
243
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 281 publications
(276 citation statements)
references
References 45 publications
12
243
0
2
Order By: Relevance
“…Therefore, these bands reveal secondary structure features and hydration level. The peculiar absence of intra/inter chain H-bond in the (PPG) 10 structure implies a relevant effect of the hydration patter to define the super-assembly [1,6]. The position of three amide I bands in (PPG) 10 crystals (1629, 1645 and 1669 cm -1 ) is in good agreement with previous FT-IR absorption spectra of (PPG) 10 solution [29].…”
Section: Amide Bandssupporting
confidence: 87%
See 4 more Smart Citations
“…Therefore, these bands reveal secondary structure features and hydration level. The peculiar absence of intra/inter chain H-bond in the (PPG) 10 structure implies a relevant effect of the hydration patter to define the super-assembly [1,6]. The position of three amide I bands in (PPG) 10 crystals (1629, 1645 and 1669 cm -1 ) is in good agreement with previous FT-IR absorption spectra of (PPG) 10 solution [29].…”
Section: Amide Bandssupporting
confidence: 87%
“…Here, up and down puckerings correspond to the negative and positive values of χ 1 dihedral angles, respectively. This strict dependence of proline puckering on its position in the triplet was first observed at 100 K inside the (PPG) 10 crystals for the inner proline residues [1], though the equivalent structure for (PPG) 9 revealed that five proline residues at the Y position are in a down puckering conformation [4].…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations